Vachellia tortilis leaf meal improves antioxidant activity and colour stability of broiler meat - Mthethwa Nomalungelo; Moyo Mehluli; Mkwanazi Mbusiseni Vusumuzi; Ndlela Sithembile Zenith; Khanyile Mbongeni; Mwale Marizvikuru; Chimonyo Michael (Open Agriculture, 2025)
The study assessed the response to antioxidant activity (AA) and chemical stability of meat produced from broilers fed on Vachellia tortilis leaf meal (VTLM). A total of 180 14-day-old chicks were randomly allocated to six diets (0, 30, 60, 90, 120, and 150 g/kg of VTLM) for 21 days. Birds were slaughtered at 35 days of age, and the Pectoralis major and thigh muscles were analyzed for chemical stability and physico-chemical properties. AA of meat was highest at 41%, corresponding to an inclusion level of 115 g/kg dry matter VTLM. Increasing levels of VTLM up to 125 and 117 g/kg DM in broiler diets increased a* redness and b* yellowness to maximum values of 8.7 and 19.7, respectively, for a storage period lasting 28 days. There was a quadratic response in alkaline phosphatase and albumin concentrations with increases in VTLM inclusion levels. Inclusions of 115 g/kg DM VTLM are recommended for improved AA but without improvement of colour stability of broiler meat. The lack of response in pH with increases in VTLM inclusion and AA revealed that high levels of antioxidants are required to cause a change in pH. The lack of chemical reactions suggests that there is a need to allow more time to get a reaction and explore higher levels of inclusion levels. Including VTLM at 115 g/kg DM, therefore, enhances the AA of meat.